Seismic Analysis of Tall Building with Varying Shear Wall Positions Using Linear Static Approach: A Review - Mahendra Patel; Dharmendra Prajapati (International Journal of Scientific Research in Civil Engineering, 2025)
Shear walls are essential for improving the strength and stability of tall buildings, especially in areas prone to seismic and wind forces. These vertical elements help resist lateral forces, reduce movement, and prevent structural damage during extreme events. This study looks at how different positions of shear walls impact the seismic performance of a tall reinforced concrete building, using ETABS software. The analysis compares four different layouts: a regular frame with no shear walls, a frame with shear walls at the four corners, a frame with shear walls along the perimeter, and a frame with shear walls at the core, focusing on key factors like base shear, story drift, and lateral displacement, which are critical for assessing seismic performance. The building considered in this study is an 11-story structure with dimensions of 24 m by 32 m and a total height of 35 m. The structure has a grid spacing of 4 m in both directions, with typical floor heights of 3.2 m and a bottom story height of 3 m. The shear walls, each 230 mm thick, are analyzed in different positions to see how their placement influences the building’s ability to resist seismic forces and minimize issues like torsional effects and uneven distribution of strength and stiffness. In this paper presenting review of literatures
Keywords: shear walls; seismic performance; lateral displacement; base shear; torsional effects; structural stability; linear static analysis